Anti-corrosion quick-curing functional filler, preparation method thereof and coating composition

By modifying the surface of metal powders with silicone compound and cross-linking treatment of amine-based solidification promoter, the problem of easy corrosion and fall off of metal particles in stealth coatings is solved, and the coating is highly corrosion-resistant and rapid curing is achieved, which meets the needs of rapid response and efficient combat.

CN119505590APending Publication Date: 2025-02-25AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411727471.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The metal particles in existing stealth coatings are prone to corrosion and fall off, and the coating construction and maintenance cycles are long, making it difficult to meet the needs of rapid response and efficient combat.

Method used

By modifying the surface of the metal powder with siloxane compound and assisting in modifying the amine-based solidification promoter, a stable cross-linking network is formed to improve the corrosion resistance and curing speed of the metal powder.

Benefits of technology

It achieves better corrosion resistance and rapid curing effect, adapts to the fast-paced coating construction and maintenance needs, and significantly improves the combat capabilities of military products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-corrosion quick-curing functional filler. The anti-corrosion quick-curing functional filler comprises a metal powder matrix and an amino curing accelerator connected to the surface of the metal powder matrix through a siloxane compound. Through the high surface energy adsorption effect of metal oxides and metal atoms in the metal powder matrix and the bridge effect of the siloxane compound, the metal powder matrix and the amino solidification accelerator are subjected to auxiliary connection modification, and the obtained anti-corrosion fast-solidification type functional filler has the corrosion resistance and the fast solidification effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of filler surface treatment, and in particular to an anti-corrosion fast-curing functional filler and a preparation method and a coating composition thereof. Background Art

[0002] At present, stealth capability has become one of the important indicators for measuring the performance of modern weapons and equipment, and is the key point of competition among weapons and equipment of various countries. As a key measure to effectively improve the stealth capability, combat performance and electronic warfare capability of weapons and equipment such as missiles, ships, aircraft, and armed helicopters, the application of stealth materials has attracted increasing market attention. Among them, quick-drying stealth materials are a research direction that has attracted much attention because of their characteristics of rapid curing and rapid commissioning. This characteristic enables quick-drying stealth materials to better adapt to the increasingly severe international situation and the fast-paced and short-cycle production characteristics of military products.

[0003] In the specific application process of radar-absorbing stealth materials, later maintenance and damage repair are also very important. Due to its special performance requirements, stealth coatings are mostly filled with metal particles with a high filler ratio. In the use environment, metal particles are easily corroded and fall off, and there is also a problem of a long investment cycle. The development of anti-corrosion and quick-drying stealth materials can further shorten the military product preparation cycle and wartime maintenance cycle, and can exert stronger combat capabilities year-on-year.

[0004] Therefore, providing a filler that can improve corrosion resistance and quickly cure the coating is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0005] In view of this, the present application provides an anti-corrosion and fast-curing functional filler, which can achieve better corrosion resistance and a faster curing effect, and achieve a more perfect adaptation to the current fast-paced coating construction cycle and coating repair and maintenance work requirements.

[0006] Due to its special performance requirements, the fillers of absorbing coatings are mostly metal powders and the filler ratio is relatively high. Under the use environment, the metal powder is very easy to corrode and fall off. The research and development of anti-corrosion and quick-drying stealth materials can further shorten the military product preparation cycle and wartime maintenance cycle, and can exert stronger combat capabilities. By optimizing the processing of metal fillers, which account for the highest proportion of absorbing coatings, and developing advanced material preparation and processing technologies, the comprehensive anti-corrosion and quick-drying performance of the material is continuously improved. Therefore, the present application uses the surface treatment technology of metal powder to modify a layer of siloxane compound on the surface of the metal powder matrix to enhance the corrosion resistance of the metal powder, and uses this as a medium to assist in modifying the curing agent on the surface, and controls the amount of linking of the amine curing agent on the final metal powder by controlling the addition amount and reaction time of the intermediate bridge siloxane compound and the addition amount and reaction time of the amine curing agent, so as to achieve controllability of the curing speed, and prevent the metal powder from corrosion through deeper surface cross-linking, thereby improving the corrosion resistance of its coating.

[0007] The present application provides an anti-corrosion fast-curing functional filler, comprising a metal powder matrix and an amine-based curing agent connected to the surface of the metal powder matrix via a siloxane compound.

[0008] In some specific implementations, the siloxane compound includes, but is not limited to, one or more of propyltriethoxysilane, diethoxydimethylsilane or 3-mercaptopropyltriethoxysilane. The present application has no special requirements for the selection of the siloxane compound. The surface of the metal powder is exposed to a siloxane compound solution, and the ethoxy group (-OEt) in the siloxane compound is hydrolyzed with the hydroxyl group on the surface of the metal powder to form a silicon-oxygen bond (Si-OM), and the siloxane compound is firmly attached to the surface of the metal powder matrix, providing a reaction site for further modification of the amine-based solidifying agent; the amine-based solidifying agent includes but is not limited to one or more of aliphatic amine-based solidifying agents, aromatic amine-based solidifying agents, alicyclic amine-based solidifying agents, polyamide amine-based solidifying agents, imidazole amine-based solidifying agents or polyamine composite solidifying agents. The present application has no special requirements for the selection of amine-based solidifying agents. The aliphatic amine-based solidifying agent includes one or more of ethylenediamine, diethylenetriamine or triethylenetetramine; the aromatic amine-based solidifying agent includes one or more of meta-phenylenediamine, diaminodiphenylmethane or 4,4'-diaminodiphenyl ether; the alicyclic amine-based solidifying agent includes isophoronediamine and / or methylhexanediamine. The surface of the metal powder modified with the siloxane compound is immersed in an amine-based curing agent solution. The amine groups in the amine-based curing agent can react with the amine groups or other residual active groups on the silane layer to form covalent bonds or weak non-covalent interactions, further stabilizing the attachment of the amine-based curing agent to the surface of the metal powder. Through the interaction, a stable cross-linked network is formed on the metal surface. In some specific implementations, the siloxane compound should maintain a moisture content of less than 1000 ppm.

[0009] In some specific implementations, the mass ratio of the metal powder matrix, the siloxane compound and the amine-based curing agent is (50-100):(1-2):10.

[0010] The present application also provides a method for preparing an anti-corrosion fast-curing functional filler, comprising:

[0011] The metal powder matrix is ​​modified by using a siloxane compound to obtain a metal powder modified by the siloxane compound;

[0012] The metal powder modified by the siloxane compound is mixed with an amino-based solidifying agent and subjected to a reflux treatment to obtain an anti-corrosion fast-curing functional filler.

[0013] In some specific implementations, the use of a siloxane compound to modify a metal powder matrix includes: washing the metal powder to obtain a metal powder matrix, mixing the metal powder with the siloxane compound, and performing a hydrolysis reaction to obtain a metal powder modified with the siloxane compound.

[0014] The present application first needs to clean the metal powder. In some specific implementations, the metal powder matrix is ​​obtained by cleaning the metal powder; the cleaning process includes mixing the metal powder with a cleaning solvent, performing reflux cleaning, and obtaining a metal powder matrix; the metal powder includes one or more of carbonyl iron micropowder, iron silicon chromium alloy powder, or iron silicon aluminum alloy powder; the cleaning solvent includes one or more of hydroxyl-containing solvents, acids, or plasmas; the hydroxyl-containing solvents include, but are not limited to, one or more of methanol, ethanol, ethylene glycol, or isopropanol, and the present application has no special requirements for the selection of hydroxyl-containing solvents; the acids include, but are not limited to, inorganic acids and / or organic acids, and the present application has no special requirements for the selection of acids, the inorganic acids include hydrochloric acid and / or sulfuric acid, and the organic acids include one or more of oxalic acid, citric acid, or acetic acid; the plasma includes, but is not limited to, one or more of oxygen plasma, argon plasma, or water vapor plasma, and the present application has no special requirements for the selection of plasmas. First, remove pollutants, processing oils and some oxides on the surface of the metal powder by acid washing, plasma washing or solvent washing to ensure the surface is clean. The treated metal powder surface will expose the hydroxyl groups or adsorbed hydroxyl groups connected to the oxide layer, providing reaction sites for subsequent reactions. In some specific implementations, the temperature of the reflux washing is 60°C to 120°C, preferably 70°C to 110°C, and more preferably 80°C to 90°C; the mass ratio of the metal powder to the washing solvent is 5:3 to 2.5:1, preferably 1.8:1 to 2.3:1, and more preferably 1.9:1 to 2.1:1. In some specific implementations, the washing treatment also includes a drying treatment. In some specific implementations, the temperature of the drying treatment is 75°C to 90°C, preferably 80°C to 85°C. In some specific implementations, the drying treatment also includes filtration using anhydrous ethanol before the drying treatment.

[0015] The present application then mixes the metal powder matrix with the siloxane compound, performs a hydrolysis reaction, and obtains a metal powder modified with the siloxane compound. In some specific implementations, the mass ratio of the metal powder to the siloxane compound is 50:1 to 100:1, preferably 60:1 to 80:1. In some specific implementations, the temperature of the hydrolysis reaction is 60°C to 120°C, preferably 70°C to 110°C, and more preferably 80°C to 90°C; the time of the hydrolysis reaction is 4h to 8h, preferably 4h to 6h. In some specific implementations, the hydrolysis reaction also includes a drying treatment. In some specific implementations, the temperature of the drying treatment is 75°C to 90°C, preferably 80°C to 85°C. In some specific implementations, cooling to room temperature is also included before the drying treatment.

[0016] The present application then mixes the metal powder modified by the siloxane compound with the amine solidifying agent, performs a reflux treatment, and obtains an anti-corrosion fast-curing functional filler. In some specific implementations, the mass ratio of the amine solidifying agent to the metal powder modified by the siloxane compound is 1:5 to 1:10, preferably 1:6 to 1:8; the temperature of the reflux treatment is 60°C to 120°C, preferably 70°C to 110°C, and more preferably 80°C to 90°C; the time of the reflux treatment is 4h to 8h, preferably 5h to 7h. In some specific implementations, the reflux treatment also includes a drying treatment. In some specific implementations, the temperature of the drying treatment is 75°C to 90°C, preferably 80°C to 85°C. In some specific implementations, the drying treatment also includes cooling to room temperature before the drying treatment. The purpose of drying is to keep the filler dry, and storage should avoid excessive humidity to reduce the consumption of moisture on the amine solidifying agent. In some specific implementations, the metal powder modified with the siloxane compound is dissolved in an ethanol solution, and then an amine-based curing agent is added. The rate of adding the amine-based curing agent should be 5 to 10 drops per second.

[0017] The present application finally performs post-processing on the filler to obtain an anti-corrosion and fast-curing functional filler. In some specific implementations, ethanol is used to clean the filler. Anhydrous ethanol solvent is used for flow cleaning again to remove unreacted amine-based curing agents to avoid the residual amine-based curing agents causing the resin to cure too quickly or uncontrollably. The cleaned metal powder is dried at 80°C for 12 hours or subjected to mild heat treatment to ensure its stability.

[0018] The present application uses siloxane compounds to assist activation and utilizes chemical bonding to activate the surface functional groups of the filler, so as to form an amino-based curing agent cross-linking network on the surface of the metal powder, thereby improving the anti-corrosion performance of the coating. The result is an anti-corrosion and fast-curing functional filler with simple processing operations, a simple and controllable process, a safe operation process and an adjustable curing rate.

[0019] The present application also provides a coating composition, comprising component A and component B, wherein component A comprises the above-mentioned anti-corrosion fast-curing functional filler, a resin matrix, a dispersant, a defoamer, a leveling agent and a diluent, and component B comprises an epoxy resin curing agent.

[0020] In some specific implementations, the component A includes, by mass percentage: 70% to 85% of the above-mentioned anti-corrosion fast-curing functional filler, 10% to 20% of a resin matrix, 1% to 5% of a dispersant, 1% to 5% of a defoaming agent, 1% to 5% of a leveling agent and 2% to 8% of a diluent.

[0021] In some specific implementations, the resin matrix includes but is not limited to epoxy resin DER331, and the present application has no special requirements for the selection of the resin matrix. In some specific implementations, the dispersant includes but is not limited to B0451, and the present application has no special requirements for the selection of the dispersant. In some specific implementations, the defoamer includes but is not limited to KH8099, and the present application has no special requirements for the selection of the defoamer. In some specific implementations, the leveling agent includes but is not limited to KEY09, and the present application has no special requirements for the selection of the leveling agent. In some specific implementations, the diluent includes but is not limited to one or more of xylene, ethyl acetate or acetone, and the present application has no special requirements for the selection of the diluent. In some specific implementations, the epoxy resin curing agent includes but is not limited to amine curing agents (such as TETA, DDM), anhydride curing agents (such as MTHPA, HHPA), isocyanate curing agents (such as TDI, MDI), phenolic curing agents, polyamide curing agents, etc., and the present application has no special requirements for the selection of epoxy resin curing agents. In some specific implementations, the mass percentage of the anti-corrosion fast-curing functional filler is 70% to 85%. When the anti-corrosion fast-curing functional filler is used, it accounts for 70% to 85% of the total coating mass, which can ensure the use amount of the amino curing agent.

[0022] The present application adopts siloxane compounds to build bridges on the surface of metal powder matrix, and assists in modifying the cross-linking of amino-based curing agents on metal powders to form a dense and controllable cross-linking network; through the high surface energy adsorption of metal oxides and metal atoms in metal powders, hydroxyl groups are activated on the metal surface to facilitate the binding and adsorption of siloxane compounds; utilizing the bridge effect of siloxane compounds, the metal powder and amino-based curing agents are assisted in connection and modification, and the obtained anti-corrosion and fast-curing functional filler has corrosion resistance and rapid curing effect; the dilution amount of the amino-based curing agent can be controlled by the content of the intermediate auxiliary connection siloxane compound, the amount used, and the reaction time, so as to achieve the control of anti-corrosion and fast-curing functional fillers with different degrees of fast curing. DETAILED DESCRIPTION

[0023] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0024] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0025] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the application is still operable. In addition, two or more steps or actions can be performed simultaneously.

[0026] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the present application and does not limit the scope of the present application unless the claims are set forth. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the present application.

[0027] In addition, the numerical ranges and parameters used to define the present application are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally refers to the actual value within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0028] The present application is further described below in conjunction with the following embodiments. The protection scope of the present application is not limited by the following embodiments.

[0029] Example 1

[0030] Add 4 kg of metal powder and 2500 mL of anhydrous ethanol into a 5000 mL three-necked flask, heat to 90°C, stir for 1 hour, keep the metal powder evenly stirred, then wash the metal powder with anhydrous ethanol and filter it three times, and dry it at 80°C to obtain a metal powder matrix.

[0031] 4kg of metal powder matrix, 2500mL of anhydrous ethanol and 40g of propyltriethoxysilane (APTES) were placed in a 5000mL three-necked flask, heated to 90°C, refluxed for 4h, cooled to room temperature, washed with anhydrous ethanol several times to remove excess APTES and filtered, dried at 80°C to obtain metal powder modified with siloxane compound. 4kg of metal powder modified with siloxane compound and 2500mL of anhydrous ethanol were placed in a 5000mL three-necked flask, heated to 90°C, stirred throughout the process to keep the metal powder evenly stirred, 400g of TEA was slowly added dropwise, refluxed for 4h after the addition was completed, cooled to room temperature, washed with anhydrous ethanol to remove excess TEA and filtered, dried at 80°C to obtain metal powder modified with amine solidifying agent.

[0032] The metal powder modified with the amino solidifying agent was again flow-washed with anhydrous ethanol, and the washed metal powder was dried at 80° C. for 12 h and sealed to obtain an anti-corrosion fast-curing functional filler 1.

[0033] Anti-corrosion fast-curing functional filler 1 was used as the absorbent, and the mass ratio of the solid filler was controlled at 80%; epoxy resin DER331 was used as the resin matrix, and the mass ratio was controlled at 15%; 1% dispersant B0451, 1% defoamer KH8099 and 1% leveling agent KEY09, and the diluent was 2% xylene solution. The above raw materials were mixed and ground as component A, and the epoxy resin curing agent was used as component B, and xylene was used as the diluent to prepare the spray sample.

[0034] Example 2

[0035] Add 4 kg of metal powder and 2500 mL of anhydrous ethanol into a 5000 mL three-necked flask, heat to 90°C, stir for 1 hour, keep the metal powder evenly stirred, then wash the metal powder with anhydrous ethanol and filter it three times, and dry it at 80°C to obtain a metal powder matrix.

[0036] 4kg of metal powder matrix, 2500mL of anhydrous ethanol and 80g of APTES were placed in a 5000mL three-necked flask, heated to 90°C, refluxed for 4h, cooled to room temperature, washed off the excess APTES and filtered, and dried at 80°C to obtain metal powder modified with siloxane compound. 4kg of metal powder modified with siloxane compound and 2500mL of anhydrous ethanol were placed in a 5000mL three-necked flask, heated to 90°C, stirred throughout the process, and the metal powder was stirred evenly. During this period, 800g of TEA was slowly added dropwise. After the addition was completed, the reflux treatment was maintained for 8h. After cooling to room temperature for one hour, the metal powder was washed off with anhydrous ethanol to remove the excess TEA and filtered, and dried at 80°C to obtain metal powder modified with an amine-based solidifying agent.

[0037] The metal powder modified with the amino solidifying agent was again flow-washed with anhydrous ethanol solvent, and the washed metal powder was dried at 80° C. for 12 hours and sealed to obtain the anti-corrosion fast-curing functional filler 2.

[0038] Anti-corrosion fast-curing functional filler 2 was used as the absorbent, and the mass ratio of the solid filler was controlled at 80%. Epoxy resin DER331 was used as the resin matrix, and the mass ratio was controlled at 15%. 1% dispersant B0451, 1% defoamer KH8099 and 1% leveling agent KEY09, and the diluent was 2% xylene solution. The above raw materials were mixed and ground as component A, and the epoxy resin curing agent was used as component B, and xylene was used as the diluent to prepare the spray sample.

[0039] Example 3

[0040] Add 4 kg of metal powder and 2500 mL of 3.5% oxalic acid aqueous solution into a 5000 mL three-necked flask, heat to 90°C, stir for 1 hour, keep the metal powder evenly stirred, then wash the metal powder with 3.5% oxalic acid aqueous solution and filter it three times, and dry it at 80°C to obtain a metal powder matrix.

[0041] 4kg of metal powder matrix, 2500mL of anhydrous ethanol and 80g of diethoxydimethylsilane were placed in a 5000mL three-necked flask, heated to 90°C, refluxed for 4h, cooled to room temperature, washed off the excess diethoxydimethylsilane and filtered, and dried at 80°C to obtain metal powder modified with siloxane compound. 4kg of metal powder modified with siloxane compound and 2500mL of anhydrous ethanol were placed in a 5000mL three-necked flask, heated to 90°C, stirred throughout the process, and the metal powder was stirred evenly. During this period, 800g of TEA was slowly added dropwise. After the addition was completed, the reflux treatment was maintained for 8h. After cooling to room temperature for one hour, the metal powder was washed off with anhydrous ethanol to remove the excess TEA and filtered, and dried at 80°C to obtain metal powder modified with an amine solidifying agent.

[0042] The metal powder modified with the amino solidifying agent was again flow-washed with anhydrous ethanol solvent, and the washed metal powder was dried at 80° C. for 12 hours and sealed to obtain an anti-corrosion fast-curing functional filler 3.

[0043] Anti-corrosion fast-curing functional filler 3 was used as the absorbent, and the mass ratio of the solid filler was controlled at 80%. Epoxy resin DER331 was used as the resin matrix, and the mass ratio was controlled at 15%. 1% dispersant B0451, 1% defoamer KH8099 and 1% leveling agent KEY09, and the diluent was 2% xylene solution. The above raw materials were mixed and ground as component A, and the epoxy resin curing agent was used as component B, and xylene was used as the diluent to prepare the spray sample.

[0044] Comparative Example 1

[0045] Add 4 kg of metal powder and 2500 mL of anhydrous ethanol into a 5000 mL three-necked flask, heat to 90°C, stir for 1 hour, keep the metal powder evenly stirred, then wash the metal powder with anhydrous ethanol and filter it three times, and dry it at 80°C to obtain a metal powder matrix.

[0046] 4 kg of metal powder matrix, 2500 mL of anhydrous ethanol and 80 g of APTES were placed in a 5000 mL three-necked flask, heated to 90°C, refluxed for 4 hours, cooled to room temperature, the excess APTES was washed off and filtered, and dried at 80°C to obtain a metal powder modified with a siloxane compound. The APTES-modified metal powder was again flow-washed with anhydrous ethanol solvent, and the washed metal powder was dried at 80°C for 12 hours, sealed and stored to obtain a functional filler 4.

[0047] Functional filler 4 was used as the absorbent, and the mass ratio of the solid filler was controlled at 80%. Epoxy resin DER331 was used as the resin matrix, and the mass ratio was controlled at 15%. 1% dispersant B0451, 1% defoamer KH8099 and 1% leveling agent KEY09, and the diluent was 2% xylene solution. The above raw materials were mixed and ground as component A, and the epoxy resin curing agent was used as component B, and xylene was used as the diluent to prepare the spray sample.

[0048] The performance test was performed on the sprayed samples obtained in Examples 1 to 3 and Comparative Example 1, and the test method was as follows:

[0049] Coating 4 viscosity: tested according to national standard GB / T 1723;

[0050] Pull-off adhesion: tested in accordance with national standard GB / T 5210, in this coating system, it is considered that the coating is fully cured when the adhesion reaches 8MPa (the standard curing procedure is 60℃ for 12h);

[0051] Salt spray resistance: tested in accordance with national standard GB / T 1771.

[0052] The test results are shown in Table 1.

[0053] Table 1

[0054]

[0055] According to the data in Table 1, the spray sample prepared by spraying using the anti-corrosion fast-curing functional filler provided by the technical solution is significantly better than the spray sample in the comparative example under a certain curing time condition, and the curing efficiency (the curing time that can meet the index adhesion) and corrosion resistance of the coating are regulated to a certain extent by controlling the reaction time and the amount of reactant added during the preparation of the filler. For example, the amount of reactant added in Examples 2 and 3 is larger, the amount of connection between the siloxane compound and the curing promoter on the metal surface is larger, the applicable period is shorter (the curing rate is faster), the time required for complete curing at room temperature is shorter, and the surface state is maintained longer under the salt spray corrosion test. In the comparative example, since the hinge coating of the curing promoter on the surface of the metal powder is not performed, the curing rate and corrosion resistance of the coating are poor.

[0056] The above is only a preferred specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can make equivalent substitutions or changes within the technical scope disclosed in the present application according to the technical solution and application concept of the present application, which should be covered by the protection scope of the present application.

Claims

1. An anti-corrosion fast-curing functional filler, characterized in that: The invention comprises a metal powder matrix and an amine-based curing agent connected to the surface of the metal powder matrix through a siloxane compound.

2. The anti-corrosion fast-curing functional filler according to claim 1, characterized in that: The siloxane compound includes one or more of propyltriethoxysilane, diethoxydimethylsilane or 3-mercaptopropyltriethoxysilane.

3. The anti-corrosion fast-curing functional filler according to claim 1, characterized in that: The amine-based solidifying agent includes one or more of aliphatic amine-based solidifying agent, aromatic amine-based solidifying agent, alicyclic amine-based solidifying agent, polyamide amine-based solidifying agent, imidazole amine-based solidifying agent or polyamine composite solidifying agent; the aliphatic amine-based solidifying agent includes one or more of ethylenediamine, diethylenetriamine or triethylenetetramine; the aromatic amine-based solidifying agent includes one or more of meta-phenylenediamine, diaminodiphenylmethane or 4,4'-diaminodiphenyl ether; the alicyclic amine-based solidifying agent includes isophoronediamine and / or methylhexanediamine.

4. The anti-corrosion fast-curing functional filler according to claim 1, characterized in that: The mass ratio of the metal powder matrix, the siloxane compound and the amine-based curing agent is (50-100): (1-2):

10.

5. A method for preparing an anti-corrosion fast-curing functional filler, characterized in that: include: The metal powder matrix is ​​modified by using a siloxane compound to obtain a metal powder modified by the siloxane compound; The metal powder modified by the siloxane compound is mixed with an amino-based solidifying agent and subjected to a reflux treatment to obtain an anti-corrosion fast-curing functional filler.

6. The preparation method according to claim 5, characterized in that: The method of modifying the metal powder matrix with the siloxane compound comprises: washing the metal powder to obtain the metal powder matrix, mixing the metal powder matrix with the siloxane compound, and performing a hydrolysis reaction to obtain the metal powder modified with the siloxane compound.

7. The preparation method according to claim 6, characterized in that: The temperature of the hydrolysis reaction is 60° C. to 120° C.; the time of the hydrolysis reaction is 4 h to 8 h.

8. The preparation method according to claim 5, characterized in that: The temperature of the reflux treatment is 60° C. to 120° C.; the time of the reflux treatment is 4 h to 8 h.

9. A coating composition, characterized in that: The invention comprises component A and component B, wherein component A comprises the anticorrosive fast-curing functional filler as claimed in claims 1 to 3, a resin matrix, a dispersant, a defoamer, a leveling agent and a diluent, and component B comprises an epoxy resin curing agent.

10. The coating composition according to claim 9, characterized in that The component A comprises, by mass percentage, 70% to 85% of the anti-corrosion fast-curing functional filler as claimed in claims 1 to 3, 10% to 20% of a resin matrix, 1% to 5% of a dispersant, 1% to 5% of a defoamer, 1% to 5% of a leveling agent and 2% to 8% of a diluent.